Penerapan Teknik Polymerase Chain Reaction (PCR) dalam Mendeteksi Bakteri Patogen pada Sektor Peternakan dan Kesehatan Masyarakat - Made Dwi Ambara Putra; Ni Nyoman Sri Budayanti; I Putu Bayu Mayura (Jurnal Pendidikan Biologi Undiksha, 2024)
Polymerase Chain Reaction (PCR) technology has emerged as a significant breakthrough in the detection and management of diseases in the livestock sector and public health. This study aims to evaluate the effectiveness and applications of PCR in detecting pathogens in livestock and zoonotic diseases that can transfer from animals to humans. The research adopts a literature review approach, analyzing various scientific findings related to the application of PCR in different contexts. The results demonstrate that PCR offers advantages in sensitivity, specificity, and detection speed compared to conventional methods, enabling effective early intervention to prevent disease spread. Furthermore, innovations such as digital PCR, Point-of-Care PCR systems, and real-time data integration broaden its applicability, particularly in resource-limited settings. These findings underscore the importance of continuous research and development in PCR technology to enhance disease surveillance and global health management.